Mso1p Regulates Membrane Fusion through Interactions with the Putative N-Peptide–binding Area in Sec1p Domain 1 - Weber, Marion (The American Society for Cell Biology, 2010)
Sec1p/Munc18 (SM) family proteins regulate SNARE complex function in membrane fusion through their interactions with syntaxins. In addition to syntaxins, only a few SM protein interacting proteins are known and typically, their binding modes with SM proteins are poorly characterized. We previously identified Mso1p as a Sec1p-binding protein and showed that it is involved in membrane fusion regulation. Here we demonstrate that Mso1p and Sec1p interact at sites of exocytosis and that the Mso1p–Sec1p interaction site depends on a functional Rab GTPase Sec4p and its GEF Sec2p. Random and targeted mutagenesis of Sec1p, followed by analysis of protein interactions, indicates that Mso1p interacts with Sec1p domain 1 and that this interaction is important for membrane fusion. In many SM family proteins, domain 1 binds to a N-terminal peptide of a syntaxin family protein. The Sec1p-interacting syntaxins Sso1p and Sso2p lack the N-terminal peptide. We show that the putative N-peptide binding area in Sec1p domain 1 is important for Mso1p binding, and that Mso1p can interact with Sso1p and Sso2p. Our results suggest that Mso1p mimics N-peptide binding to facilitate membrane fusion.